2002
DOI: 10.1046/j.1365-2982.2002.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motilin on human interdigestive gastrointestinal and gallbladder motility, and involvement of 5HT3 receptors

Abstract: A plasma motilin peak and a partial gallbladder emptying precede the antral phase III of the migrating motor complex (MMC). To clarify the causal relationship between these factors, we aimed to study the role of motilin in interdigestive gastrointestinal and gallbladder motility simultaneously. In addition, involvement of 5HT3 receptors in the action of motilin was studied. Eight fasting, healthy male volunteers received 13Leu-motilin or 0.9% NaCl i.v. for 30 min, in randomized order on two separate occasions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
6
21
1
1
Order By: Relevance
“…Plasma motilin shows a cyclic fluctuation during the interdigestive state and its peak is highly associated with gastric phase III contractions [36]. Motilin infusion elicits gastric phase III contractions in dogs [36] and humans [37]. Although motilin has a structural resemblance to ghrelin (both peptides share eight amino acids; 27% of ghrelin and 36% of motilin), motilin does not cause any gastric contractions in rats [38].…”
Section: Discussionmentioning
confidence: 98%
“…Plasma motilin shows a cyclic fluctuation during the interdigestive state and its peak is highly associated with gastric phase III contractions [36]. Motilin infusion elicits gastric phase III contractions in dogs [36] and humans [37]. Although motilin has a structural resemblance to ghrelin (both peptides share eight amino acids; 27% of ghrelin and 36% of motilin), motilin does not cause any gastric contractions in rats [38].…”
Section: Discussionmentioning
confidence: 98%
“…In humans, duodenal motilin receptors are probably mainly smooth muscle receptors, while the antrum probably contains both smooth muscle and neural receptor subtypes 9–12 . Motilin has also been demonstrated as stimulating agent for gallbladder emptying in the fasted state, 13 preceding an antral phase III 14 . Finally, motilin as well as erythromycin have dose‐dependent inhibitory effects on the rabbit pylorus in vitro , because of the presence of motilin receptors on pyloric muscles as well as on inhibitory neurones innervating pyloric muscle 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that a refractory period for antral stimulation by motilin is related to the origin of phase III that precedes infusion, partly based on observations of a prolonged MMC cycle after a normal antral phase III 3 . A refractory period for motilin‐induced gallbladder emptying may be absent, as we previously observed that antral and gallbladder emptying may be regulated by different mechanisms 14 . This implies that two subsequent motilin infusions probably will not initiate two subsequent antral phase IIIs, while gallbladder emptying may occur with each motilin infusion.…”
Section: Introductionmentioning
confidence: 99%
“…NO can play a role in the generation and modulation of inhibitory transmission [8]. These data suggest that NO is involved in the regulation of gastric MMC under normal conditions, but has little role in the postoperation inhibition of motor activity.…”
Section: Resultsmentioning
confidence: 80%